2017
DOI: 10.1128/mbio.01658-17
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Cleavage of Middle East Respiratory Syndrome Coronavirus nsp3-4 Polyprotein Induce the Formation of Double-Membrane Vesicles That Mimic Those Associated with Coronaviral RNA Replication

Abstract: Betacoronaviruses, such as Middle East respiratory syndrome coronavirus (MERS-CoV), are important pathogens causing potentially lethal infections in humans and animals. Coronavirus RNA synthesis is thought to be associated with replication organelles (ROs) consisting of modified endoplasmic reticulum (ER) membranes. These are transformed into double-membrane vesicles (DMVs) containing viral double-stranded RNA and into other membranous elements such as convoluted membranes, together forming a reticulovesicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
238
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 206 publications
(246 citation statements)
references
References 65 publications
7
238
1
Order By: Relevance
“…However, given the prevalence of DMSs and CM across different CoV genera, it is tempting to speculate that these structures must play a role in virus replication. It has been proposed that CM could be a form of cubic membranes [25, 56], which are membrane aggregates resulting from ER protein overexpression [57]. CM, which abundantly label for viral nsps [15, 20] and proliferate late in infection [15, 20, 21], could thus be a by-product of viral protein overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the prevalence of DMSs and CM across different CoV genera, it is tempting to speculate that these structures must play a role in virus replication. It has been proposed that CM could be a form of cubic membranes [25, 56], which are membrane aggregates resulting from ER protein overexpression [57]. CM, which abundantly label for viral nsps [15, 20] and proliferate late in infection [15, 20, 21], could thus be a by-product of viral protein overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, co-expression of SARS-CoV nsp3, nsp4 and nsp6 induced DMV formation in the transfected cells [143]. A more recent study showed that, for both MERS-CoV and SARS-CoV, co-expression of nsp3 and nsp4 was already sufficient to induce DMV formation [144]. On the other hand, overexpression of coronavirus nsp6 induced the formation of autophagosomes [145], but at the same time restricted its expansion [146].…”
Section: Glycosylation Of Nsp3 and Nsp4mentioning
confidence: 99%
“…Also, the negative-stranded RSV genome and its replication enzymes are found associated with cytosolic occluded structures, in that case named inclusion bodies [38,39]. Expression of a selection of specific hydrophobic viral proteins can usually mimic the formation of these structures, for example, nsp3 and nsp4 of CoVs [40], the N and P proteins of RSV [41], and 2B,2C and 3A proteins of enterovirus (polio; [42]). All these structures, while divers in morphology and contents, seem to concentrate the viral replication machinery, intermediates and products inside membrane-bound vesicles or invaginations, seemingly unreachable for the innate immune sensors of the cytosol.…”
Section: Shielding Away the Dangerous Goods In The Replication Organellementioning
confidence: 99%